3-[(Dodecylthiocarbonyl)Methyl]-Glutarimide Attenuates Graft Arterial Disease by Suppressing Alloimmune Responses and Vascular Smooth Muscle Cell Proliferation. Issue 5 (May 2015) - Zaitsu, Masaaki; Yamashita, Kenichiro; Shibasaki, Susumu; Tsunetoshi, Yusuke; Fukai, Moto; Ogura, Masaomi; Yoshida, Tadashi; Igarashi, Rumi; Kobayashi, Nozomi; Umezawa, Kazuo; Todo, Satoru
Abstract : Background: Graft arterial disease (GAD) is a major cause of late graft loss after organ transplantation. Alloimmune responses and vascular remodeling eventually cause the transplant organ to develop GAD. In this study, we aimed to limit the development of GAD by inhibiting alloimmune responses and vascular smooth muscle cell (VSMC) proliferation with a new compound, 3-[(dodecylthiocarbonyl)methyl]-glutarimide ([DTCM]-glutarimide), in a murine cardiac model of GAD. Methods: The hearts from B6.CH-2 bm12 mice were transplanted into C57BL/6 mouse recipients to examine the extent of GAD. The recipients were treated with either vehicle or DTCM-glutarimide intraperitoneally (40 mg/kg per day) for 4 weeks. Results: The administration of DTCM-glutarimide attenuated GAD formation (luminal occlusion: 37.9 ± 5.9% vs 14.8 ± 5.4%, P < 0.05) by inhibiting the number of graft-infiltrating cells and decreasing alloreactive interferon (IFN)-γ production compared with control mice, as measured by the Enzyme-linked ImmunoSpot assay. In vitro, VSMCs proliferated on stimulation with either basic fibroblast growth factor or IFN-γ and splenocytes after transplantation, but the addition of DTCM-glutarimide resulted in the inhibition of VSMC proliferation. Moreover, DTCM-glutarimide suppressed cyclin D1 expression and inhibited cell cycle progression from G1 to S in VSMCs. Conclusions: The compound DTCM-glutarimide suppressed GAD development by inhibiting not only alloimmune responses but also VSMC proliferation in the graft. Abstract : Graft vasculopathy continues to be a significant clinical problem. This experimental study presents data on a DTCM-glutarimide reducing vasculopathy. Supplemental digital content is available in the text.